Implementation and Characterization of Flow Injection in Dissolution DNP-NMR - Chen, Hsueh-Ying (Chemphyschem, 2015)
Dissolution dynamic nuclear polarization (D-DNP) offers a substantial signal increase for liquid state NMR. A challenge in realizing the possible gain lies in the transfer of the hyperpolarized sample to the NMR detector without loss of hyperpolarization. Here, we demonstrate that a flow injection method using high pressure liquid leads to improved performance compared to the more common gas driven injection, by suppressing residual fluid motions during the NMR experiment while still achieving short injection time. Apparent diffusion coefficients were determined from pulsed field gradient echo measurements, and were shown to fall below 1.5x the value of a static sample within 0.8 s. Due to the single-scan nature of D-DNP, pulsed field gradients are often the only choice for coherence selection or encoding, but their application requires stationary fluid. Sample delivery driven by a high-pressure liquid will improve the applicability of these types of advanced experiments in D-DNP.